Ball tracking in football - Ball, K.; Haycraft, J.; Bright, L.; Robertson, S.; Billingham, J.; Evans, N.; Aughey, R. (ISBS Proceedings Archive (Michigan), 2022)
This study outines the evaluation of VICON TRACKER software in tracking a ball in a large test area. A 22 camera VICON system and VICON Tracker software was used to track a soccer ball both indoor (22 m x 12 m) and outdoor (22 m x 28 m). Different ball marker setups were evaluated for accuracy and percentage data capture manipulating the number and type of reflective markers, as well as software settings, ands whether the system identified the centre of the ball. TRACKER achieved greater than 90% data capture percentage using the half dome markers or nine flat marker setups. Importantly a pre-test setup of the ball object and a 200 Hz (as opposed to 100 Hz) sample rate was needed. The ball centre was also captured by the software. Future work will examine if this system can perform in larger spaces and with multiple players in the area.